Diéguez, A., Transhumanismo. : La búsqueda tecnológica del mejoramiento humano. Barcelona, Ed. Herder, 2017, 248 pp. ISBN:978-84-254-3962-9. - Serra Olivero, Facundo (2019)
Fil: Serra Olivero, Facundo. Pontificia Universidad Católica Argentina; Argentina